In Vivo Mutagenic Effect of Very Low Dose Radiation - Pamela J. Sykes; Tanya K. Day; Sarah J. Swinburne; Joanne M. Lane; Alexander A. Morley; Antony M. Hooker; Madhava Bhat (SAGE Publishing, 2006)
Almost all of our knowledge about the mutational effect of radiation has come from high dose studies which are generally not relevant to public exposure. The pKZ1 mouse recombination mutagenesis assay enables study of the mutational effect of very low doses of low LET radiation (μGy to cGy range) in a whole animal model. The mutational end-point studied is chromosomal inversion which is a common mutation in cancer. We have observed 1) a non-linear dose response of induced inversions in pKZ1 mice exposed to a wide dose range of low LET radiation, 2) the ability of low priming doses to cause an adaptive response to subsequent higher test doses and 3) the effect of genetic susceptibility where animals that are heterozygous for the Ataxia Telangiectasia gene (Atm) exhibit different responses to low dose radiation compared to their normal litter-mates.